The politics of interweaving performance cultures : beyond postcolonialism - Fischer-Lichte, Erika; Jost, Torsten; Jain, Saskya Iris; Amine, Khalid; Alzate, Gastón A.; Lin, Shen; Singleton, Brian; Werry, Margaret; Lo, Jacqueline; Siouzouli, Natascha; Gilbert, Helen; Bharucha, Rustom; et al. (New York ; London : Routledge, 2014)
This book provides a timely intervention in the fields of performance studies and theatre history, and to larger issues of global cultural exchange. The authors offer a provocative argument for rethinking the scholarly assessment of how diverse performative cultures interact, how they are interwoven, and how they are dependent upon each other.

While the term 'intercultural theatre' as a concept points back to postcolonialism and its contradictions, The Politics of Interweaving Performance Cultures explores global developments in the performing arts that cannot adequately be explained and understood using postcolonial theory. The authors challenge the dichotomy 'the West and the rest' – where Western cultures are 'universal' and non-Western cultures are 'particular' – as well as ideas of national culture and cultural ownership.

This volume uses international case studies to explore the politics of globalization, looking at new paternalistic forms of exchange and the new inequalities emerging from it. These case studies are guided by the principle that processes of interweaving performance cultures are, in fact, political processes. The authors explore the inextricability of the aesthetic and the political, whereby aesthetics cannot be perceived as opposite to the political; rather, the aesthetic is the political.
Sadržaj: Introduction ; Part I: Strategies and dynamics ; Part II: Rituals and festivals ; Part III: Failures and resistances
Bibliografije i bibliogr. bilješke uz radove.
Imensko kazalo ; Predmetno kazalo
Keywords: izvedbene umjetnosti - 21. st. - politički aspekti; postkolinijalizam : izvedbene izmjetnosti - kazalište - 21. st; interkulturalno kazalište -- interkulturalna komunikacija; teorija kazališta - sociologija kazališta